Literacy and lettering in the rural school: a study in EJA classes at Escola Santo Antônio, Rio Bacuri, Abaetetuba, Pará (Research, Society and Development, 2021)
Literacy for young people and adults in schools located in rural areas is one of the challenges faced by teachers, who, in general, do not have specific training (graduation or specialization in the area) that can help them in their classroom practices with this audience. specific. Therefore, this article aims to investigate the pedagogical practices of youth and adult literacy adopted at the Santo Antônio Municipal School, located on the Bacurí River, region of the islands, in Abaetetuba, Pará. As a methodology, we will choose qualitative research and interview with a teacher of Youth and Adult Education and the principal of the researched school. Based on the interviews, it was evident that the literacy process at the Santo Antônio Municipal School faces several challenges ranging from class schedules that do not correspond to the availability of students, the lack of space for the development of classes, as well as the lack of professionals such as pedagogical coordination and servants, making the EJA teacher work alone, assuming all the tasks necessary for the functioning of the school space. Furthermore, it was identified that, despite the challenges faced, the teacher creates and develops different strategies that approach literacy to diversify their work, contributing to the teaching and learning process of EJA students.